Community structure and pathogenomics of Pinaceae-infecting Fusarium spp. - Dobbs, John, author; Stewart, Jane E., advisor; Kim, Mee-Sook, committee member; Sloan, Daniel B., committee member; Heuberger, Adam L., committee member (Colorado State University. Libraries, 2024)
Due to a warming climate, the need for nursery grown conifer seedlings is continually increasing. However, several Fusarium spp. that cause pre- and post-emergent damping-off and root disease can hinder production of conifer seedlings. These soil or seed-borne Fusarium pathogens of conifers infect seedlings through the developing roots, and their similar effects on conifer hosts suggests that these pathogens may share a common evolutionary history. The shared ecological function of these Fusarium pathogens is likely associated with lineage-specific (LS) chromosomes or virulence gene(s) that are shared among these species. Identifying these potentially shared chromosomes or gene(s) and their functionality is best approached through the use of multiple 'omics technologies. Taken together, genomics, transcriptomics, proteomics, and metabolomics provide a comprehensive overview of the plant-microbial interactions at the time of Fusarium infection. This research accentuates how a combination of these technologies, such as genomics and transcriptomics, can be used to elucidate the biology of Fusarium pathogens and identify the presence of virulence-associated LS chromosomes or virulence gene(s) that facilitate the development of tools to rapidly identify and track these important pathogens. Chapter two, published in Frontiers in Plant Science, presents the observed regional effect on community structure of Fusarioid fungi collected from conifer seedlings among nurseries across the contiguous USA. The need for a global consensus to establish and maintain databases based on Fusarioid species type strains as references due to the continuing taxonomic disputes about the appropriate classification of Fusarium spp. designations was also discussed. For this reason, phylogenetic placement of the isolates was used for species identification; however, it is recognized that more research, such as whole genome sequencing, is needed to further validate the taxonomic identify of the isolates used in this study. Chapter three presents the whole genome comparisons of 17 Fusarium spp. isolates collected from conifer seedlings. Based on phylogenetic analyses of 16 conserved loci and composition of predicted genes, species were shown similar within and among Fusarium species complexes. Putative profiles of pathogenicity/virulence genes, including secreted in xylem (SIX) genes 2, 3, 9, and 14, and secondary metabolites, including the mycotoxins fumonisin and deoxynivelanol, were identified among the species complexes, but validation of expression of these genes is needed to demonstrate their functionality. Chapter four explores the mechanisms of pathogenicity and/or virulence of two understudied Fusarium spp., F. commune and F. annulatum, on conifer and non-conifer hosts and the differential gene expression in a susceptible conifer species. Further, the putative secretome profiles of Fusarium spp. within species complexes were identified, containing secreted carbohydrate-active enzymes, major facilitator supergroup transporters, apoplastic effectors, and gene products involved in secondary metabolite biosynthesis such as prolipyrone B/gibepyrone D, aurofusarin, and deoxinivelanol. Results from this study showed F. annulatum and F. commune caused disease on young conifer and non-conifer seedlings and identified putative genes associated with broad pathogenicity, and possibly indicating age-related resistance within the conifer host to certain upregulated pathogenicity genes. Due to the threat of spreading fungal pathogens from nurseries to field sites through latent infected seedlings and seed, this research highlights the need for robust early detection methods, while also providing insight into the biology of 17 Fusarium spp. that are potentially pathogenic to conifer seedlings. This research will help further develop technologies that aid managers for controlling Fusarium damping-off and root disease and mitigating the spread of novel haplotypes across regions.
Keywords: Fusarium; nurseries; transcriptomics; genomics; conifers; pathogenicity/virulence genes